2016
DOI: 10.1016/j.ijfoodmicro.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonella enterica and Listeria monocytogenes in cantaloupe puree by high hydrostatic pressure with/without added ascorbic acid

Abstract: The objective of this research was to evaluate and develop a method for inactivation of Salmonella enterica and Listeria monocytogenes in cantaloupe puree (CP) by high hydrostatic pressure (HHP). Cantaloupe being the most netted varieties of melons presents a greater risk of pathogen transmission. Freshly prepared CP with or without 0.1% ascorbic acid (AA) was inoculated with a bacterial cocktail composed of a three serotype mixture of S. enterica (S. Poona, S. Newport H1275 and S. Stanley H0558) and a mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…SSC was not affected by both thermal and ozone treatments, similar to what has been reported in the majority of published works (Mariana, Cynthia, Carin, & Rodrigo, ; Miller et al, ; Mukhopadhyay et al, ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…SSC was not affected by both thermal and ozone treatments, similar to what has been reported in the majority of published works (Mariana, Cynthia, Carin, & Rodrigo, ; Miller et al, ; Mukhopadhyay et al, ).…”
Section: Resultssupporting
confidence: 88%
“…Cantaloupe melon is a commonly consumed fruit worldwide due to its nutritional and organoleptic properties, being recognized as a good source of bioactive compounds, with a desirable flavor, appreciated texture, and low caloric value (Mukhopadhyay et al, ). Due to these healthy and sensorial properties, together with high water content and sugar concentration, Cantaloupe melon is extensively used as a raw material in the fruit juices industry.…”
Section: Introductionmentioning
confidence: 99%
“…(). Ascorbic acid acts as an oxygen scavenger for the removal of molecular oxygen in enzymatic reactions (Mukhopadhyay et al ., ). During the storage, all samples showed ascorbic acid degradation, and the ascorbic acid content of RF‐treated sample was higher than that in the TP sample during the storage.…”
Section: Resultsmentioning
confidence: 97%
“…According to Buzrul et al (), HPP treatment caused injury to a large proportion of the cells, resulting in reduced resistance to low pH. Mukhopadhyay et al () evaluated the inactivation of L. monocytogenes in melon puree (pH: 6.9) treated with HPP, during 10 days of storage at 4 °C. They observed that bacteria count remained stable on control samples, associating this behavior to an antagonistic interaction with the native microbiota of the product.…”
Section: Resultsmentioning
confidence: 99%
“…The study of the impact of preservation treatments on the evolution of quality factors during storage of complex matrices such as mixed F&V smoothies remains largely unexplored and, since has become one of the food industry sectors with the highest growth worldwide (Morales‐de la Peña et al, ), is an issue that needs to be properly addressed. Therefore, the objective of this research was to study the stability of a F&V smoothie treated with previously optimized HPP conditions during refrigerated storage.…”
Section: Introductionmentioning
confidence: 99%